- #1

- 3

- 0

Hi, I've Read an Article That Says:

If:

EQ.1:

and EQ2:

http://latex.codecogs.com/gif.latex?x=vtcos(\theta)

and EQ3:

http://latex.codecogs.com/gif.latex?y=-\frac{1}{2}gt^2 + vtsin(\theta)

We Can Get The Following Equation (an Ellipse Equation) By Substituting

http://latex.codecogs.com/gif.latex?(y-\frac{v^2}{4g})^2 + \frac{1}{4}x^2=(\frac{v^2}{4g})^2

But How it is Possible?!

If:

EQ.1:

and EQ2:

http://latex.codecogs.com/gif.latex?x=vtcos(\theta)

and EQ3:

http://latex.codecogs.com/gif.latex?y=-\frac{1}{2}gt^2 + vtsin(\theta)

We Can Get The Following Equation (an Ellipse Equation) By Substituting

**(EQ1) into EQ.2 and EQ.3 Using StraightForward Algebra:***t*http://latex.codecogs.com/gif.latex?(y-\frac{v^2}{4g})^2 + \frac{1}{4}x^2=(\frac{v^2}{4g})^2

But How it is Possible?!

Last edited: